The effect of a student–teacher–scientist partnership program on high school students' science achievement and attitudes about scientists. Issue 3 (10th November 2021) - Taylor, Joseph A.; Adams, Catrina T.; Westbrook, Anne L.; Creasap Gee, Jodi; Spybrook, Jessaca K.; Kowalski, Susan M.; Gardner, April L.; Bloom, Mark
Abstract: This article describes the effects of a student–teacher–scientist partnership program on high school students' science outcomes. The design was a cluster‐randomized trial with an analytic sample of 36 teachers randomly assigned to teach a photosynthesis‐ and respiration‐focused module including student‐designed investigations supported by online mentoring from scientists. Forty‐nine teachers were randomly assigned to teach photosynthesis and respiration to students as they normally would. The core finding was that implementing the module in combination with the online mentoring resulted in significant effects on student achievement (effect size = 0.284) and attitudes toward scientists (effect size = 0.280). The study sample was highly representative, demographically, to the US population of high schools. Future research should replicate the current study design, with the current and other related interventions, while examining component‐specific costs and efficacy. Related studies should also examine the relationship between the quality of scientist–student dialogue and student outcomes.